After ΠiΣtiΣ XpiΣtoy: Neglected Evidence from the Apostolic Fathers - Whitenton, Michael R. (The journal of theological studies, 2010)
What light do the Apostolic Fathers shed on the perennial debate over the (Gal. 2:16 [twice], 20; 3:22; Rom. 3:22, 26; Phil. 3:9; cf. Eph. 3:12 [τῆς πίστεως αὐτῦ]; 4:13)? While it is often asserted that the early Church Fathers did not speak of the faithfulness of Jesus, a complete analysis of similar constructions in the Apostolic Fathers has yet to be registered. Setting out to fill this gap, this article investigates every use of πίστς with a personal genitive in the Apostolic Fathers and includes an exegesis of the texts that may speak of Jesus’ own faithfulness. Against the scholarly consensus, this article concludes that the Apostolic Fathers did indeed speak of the faithfulness of Jesus Christ, as well as a faith as something enigmatically mediated through him.